Effectiveness of The Newborn Behavioral Observation (NBO) System in Improving Mother and Infant Interaction - Windarti, Siti Wahyu; Suryawan, Ahmad (Folia Medica Indonesiana, 2021)
The interaction of mother and infant is a fundamental basis for the development of the infant. It can also determine the success of the baby in the future. About 4 out of 10 infants experience problems interacting with their parents. The NBO system was created to sensitize parents on their infant's competencies to help them understand their infant's behavior, and promote positive interactions between parents and their new infant. This study aimed to evaluate the effectiveness of the NBO system to improve mother-infant interactions and find out the mothers' knowledge about their infant's behavior when participating in this observation. This study was a cross-sectional study consisting of all the newborns and their mothers admitted to the Dr. Soetomo General Academic Hospital Surabaya from May 2019 to January 2020 who met the inclusion criteria. Mothers and infants participated in the NBO within 1-3 days after delivering their infants and one month postpartum for the second NBO. The NBO was carried out with 35 mothers and infants. The mothers' age was on average 28.5±5.98 years old, multiparous mothers accounted for 71.4%, most infants were male (65.7%), the median gestational age was 38 weeks with the median birth weight 2900 grams. The median score of mothers' knowledge about their infants before the NBO session was 2 (1-6). After the session, these median scores increased to 7 (5–10) significantly (p<0.001). The NBO system was significant to strengthen mother-infant interaction and increased the mothers' knowledge about their infants' behavior.